Hak kekayaan Intelektual pada Bisnis Pariwisata Di Kota Wisata Sungai Penuh dan Kabupaten Kerinci - Firya Oktaviarni; Dwi Suryahartati (Universitas Batanghari Jambi, 2020)
The city of Sungai Penuh and Kerinci Regency rely on tourism as a source of regional income supported by natural beauties and cultural diversity of the local communities. Utilizing the potential of nature and culture as assets of regional financial income requires a variety of supporting business components, including hotels, restaurants, culinary, travel agencies, craft arts and its products, performing arts and natural tourism and so on, where all these components shall be utilized optimally. Legal protection of Intellectual Property Rights is needed as well. Based on that, the main legal problem raised in this article is the application of Intellectual Property Rights in the tourism business in the city of Sungai Penuh and Kerinci Regency. This article is sociological juridical study using the qualitative analysis method and both primary and secondary data as research materials. It is shown that the existence of intellectual property rights in both regions has not exercised optimally as there are lacks of understanding on the importance of the existence of intellectual property rights as part of legal protection for local assets in the tourism business in Indonesia. The local governments, supported by academics, shall socialise the importance of intellectual property rights to the community by using the local wisdom approach.